(3GdCSWM GdNVQGA aj GdEScGf (B: s (3OQGSI dRQGYI CSWM GdeHGfj GdbGFeI aj GdefGWb PGJ GdcKGaI GdScGfjI GdYGdjI (B/ s - (3OjfG YjO SYjO NGWQs; (3CMeO QVG YGHOjf (B: s; (3CMeO eMeO Cejf (B: s ((3GdbGgQI (B: s (3OjfG YjO SYjO NGWQ (B: s, 2014)
(3JJWQb GdQSGdI Gdj WQM GdCSWM GdNVQGA ceONd jSge aj JYhjV fOQI GdeSWMGJ GdNVQGA aj GdefGWb PGJ GdcKGaI GdScGfjI GdYGdjI(B. (3aJfGbT eaghe GdeSMGJ GdNVQGA hCgejJgG GdhXjajI hcja JJcGed eY GdHjFI GdeTjOI hJYed Ydj JMSjf GOGFjJgG(B. (3hYf WQjb OQGSI GdCfXeI GdEfTGFjI dfXe GdJNVjQ GdQCSj hJMdjd hJUfja GdCSWM GdNVQGA jJe GdJhUd Gdj bGFeI eQLYjI dCSS hVhGHW JUejegG(B. (3hCNjQkG(B: (3ef NdGd GdOQGSI GdejOGfjI(B: (3jJe OQGSI hJMdjd GdaQVjI GdHMKjI heWGHbI JLQHI GdMOGFb GdeKeQI aj GdOQH GdCMeQ HGdbGFeI GdeQLYjI Yf WQjb GSJHjGf GdbGFejf Ydj Jdc GdJLQHI(B. (3hef Ke Jbjje fJGFL GdESJHjGf HGdfXGe GdESJQGJjLj Ph GdCQHYI CQcGf (B"SWOT". (3hjJe GSJNdGU GdfJGFL hGdJhUjGJ GdJj JgOa YGeI Gdj JYeje GdCSWM GdNVQGAs
(3GWQhMI (B((3eGLSJjQ (B) - (3LGeYI GdbGgQI (B- (3cdjI GdgfOSI (B- (3bSe GdgfOSI GdeYeGQjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCSWM GdNVQGAs; (3GdJNVjQ GdQCSjs; (3GdbGFeI GdeQLYjIs